Peningkatan Kapasitas Tutor Bahasa Inggris dan Manajemen Pengelolaan Kampung Inggris di Desa Tete Batu, Lombok Timur - Rahmat, Hery; Rahman, Kasyfur (Sasambo: Jurnal Abdimas (Journal of Community Service), 2025)
Tete Batu Village is one of the villages that was developed into a Desa Wisata (vourism village) in Lombok Timur regency, West Nusa Tenggara province. To support this program, the regency government launched the Kampung Inggris Tete Batu (KITB) program. However, KITB program has not run optimally as the capacity lack of the program’s operators in term of tutors’ ability to implement learning method and evaluation system as well as the inappropriately management program. Therefore, in general this community service activity using the Asset Based Communities Development (ABCD) method is aimed to support the community independence in this case KITB to carry out good English course. Specifically, the community service is pointed to strengthen the capacity of English tutors and course management through KITB program in supporting tourism in Tete Batu village, Lombok Timur Regency. This community service activities are held through Focus Group Discussion (FGD), materials delivering related to curriculum development and learning materials as well as reflection. The results of this community service indicate an increasing understanding toward the importance of curriculum and appropriate material development in the KITB management as well as a simple analysis of weaknesses, and opportunities for institutional development